Validation of the Portuguese version of the Evidence-Based Practice Questionnaire - Rui Pedro Gomes Pereira; Ana Cristina Pinheiro Guerra; Maria José da Silva Peixoto de Oliveira Cardoso; Alzira Teresa Vieira Martins Ferreira dos Santos; Maria do Céu Aguiar Barbieri de Figueiredo; António Cândido Vaz Carneiro (Universidade de São Paulo, 2015)
OBJECTIVES: to describe the process of translation and linguistic and cultural validation of the Evidence Based Practice Questionnaire for the Portuguese context: Questionário de Eficácia Clínica e Prática Baseada em Evidências (QECPBE). METHOD: a methodological and cross-sectional study was developed. The translation and back translation was performed according to traditional standards. Principal Components Analysis with orthogonal rotation according to the Varimax method was used to verify the QECPBE's psychometric characteristics, followed by confirmatory factor analysis. Internal consistency was determined by Cronbach's alpha. Data were collected between December 2013 and February 2014. RESULTS: 358 nurses delivering care in a hospital facility in North of Portugal participated in the study. QECPBE contains 20 items and three subscales: Practice (α=0.74); Attitudes (α=0.75); Knowledge/Skills and Competencies (α=0.95), presenting an overall internal consistency of α=0.74. The tested model explained 55.86% of the variance and presented good fit: χ2(167)=520.009; p = 0.0001; χ2df=3.114; CFI=0.908; GFI=0.865; PCFI=0.798; PGFI=0.678; RMSEA=0.077 (CI90%=0.07-0.08). CONCLUSION: confirmatory factor analysis revealed the questionnaire is valid and appropriate to be used in the studied context.